Atlantic salmon possesses two clusters of type I interferon receptor genes on different chromosomes, which allows for a larger repertoire of interferon receptors than in zebrafish and mammals - Sun, Baojian; Greiner-Tollersrud, Linn; Koop, Ben F.; Robertsen, Børre (Developmental & Comparative Immunology, 2014)
Mammalian type I interferons (IFNs) signal through a receptor composed of the IFNAR1 and IFNAR2 chains. In zebrafish two-cysteine IFNs utilize a receptor composed of CRFB1 and CRFB5, while four-cysteine IFNs signal through a receptor formed by CRFB2 and CRFB5. In the present work two CRFB clusters were identified in different chromosomes of Atlantic salmon. Genes of three CRFB5s, one CRFB1, one CRFB2 and the novel CRFB5x were identified, cloned and studied functionally. All CRFBs were expressed in 10 different organs, but the relative expression of CRFBs varied. Mx-reporter assay was used to study which CRFBs might be involved in receptors for salmon IFNa, IFNb and IFNc. The results of Mx-reporter assays suggest that IFNa signals through a receptor composed of CRFB1a as the long chain and either CRFB5a, CRFB5b or CRFB5c as the short chain; IFNc signals through a receptor with CRFB5a or CRFB5c as the short chain while IFNb may signal through a receptor with CRFB5x as a short chain. Taken together, the present work demonstrates that Atlantic salmon has a more diverse repertoire of type I IFN receptors compared to zebrafish or mammals. This work was supported by the Regional Research Fund for Northern Norway (grant 212426), Tromsø Research Foundation (grant A37036) and NSERC (BFK). Faculty Reviewed